2023
DOI: 10.1186/s13690-023-01038-x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists’ involvements and barriers in the provision of health promotion services towards noncommunicable diseases: Community-based cross-sectional study in Northwest Ethiopia

Abstract: Background Community drug retail outlets (CDROs) are among the initial healthcare facilities where pharmacists play a crucial role in preventing and managing noncommunicable diseases (NCDs). Therefore, this study assessed pharmacists’ level of involvement and barriers in the provision of health promotion for noncommunicable diseases at CDROs in Northwest Ethiopia. Methods A community-based multicenter cross-sectional study was conducted among commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…The study also showed that only a few pharmacists had sufficient knowledge; additionally, both community and hospital pharmacists achieved poor knowledge scores. These results are consistent with the study conducted among community pharmacists in northwest Ethiopia ( Sendekie et al, 2023 ). However, some studies conducted in the same context demonstrated adequate knowledge, which diverged from the current study results ( Amadi et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…The study also showed that only a few pharmacists had sufficient knowledge; additionally, both community and hospital pharmacists achieved poor knowledge scores. These results are consistent with the study conducted among community pharmacists in northwest Ethiopia ( Sendekie et al, 2023 ). However, some studies conducted in the same context demonstrated adequate knowledge, which diverged from the current study results ( Amadi et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…These items focus on the routine, detailed activities of CPPs, including: the request for a prescription; detailed medication information in terms of dosage regimens, potential side effects, and adherence; lifestyle modifications and risky behaviours; physical activities; routine checkups for blood glucose, blood pressure, and weight; consulting of physicians for further assessment; and services provided for diabetic patients. The items were prepared after reviewing of relevant literature (Sendekie et al, 2023 ; Erku et al, 2017 ; Belachew et al, 2020 ; Yousuf et al, 2019 ; Teka & Baye, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The roles of community pharmacist in public healthcare services have grown and expanded. They are making more direct interventions in disease management, medication education, and preventative actions (Omboni & Caserini, 2018 ; George et al, 2010 ; Sendekie et al, 2023 ; Laliberté et al, 2012 ). Direct interventions can be used to provide people in the area with pharmaceutical treatments immediately.…”
Section: Introductionmentioning
confidence: 99%
“…7 The biggest challenges include a lack of qualified pharmacists, a lack of standard practice guidelines for counseling and medicationrelated issues, and a lack of public understanding of the pharmacist's role in healthcare. [8][9][10][11] An earlier study conducted by Asrade et al showed that being busy with pharmacists and the education, experience, and attitudes of pharmacists were found to be obstacles to providing counseling. 12 Patient satisfaction is influenced by a variety of factors, including the standard of clinical care delivered, the availability of medications, the conduct of medical professionals, the cost of services, hospital infrastructure, physical comfort, emotional support, and consideration of the preferences of the patient.…”
Section: Introductionmentioning
confidence: 99%
“… 7 The biggest challenges include a lack of qualified pharmacists, a lack of standard practice guidelines for counseling and medication-related issues, and a lack of public understanding of the pharmacist’s role in healthcare. 8 - 11 An earlier study conducted by Asrade et al showed that being busy with pharmacists and the education, experience, and attitudes of pharmacists were found to be obstacles to providing counseling. 12…”
Section: Introductionmentioning
confidence: 99%